The Performance of Primary School Teachers In the Unit of Education Technical Implementation, Banyumanik, Semarang - Muhamad Afandi; Sari Yustiana (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
The purpose of this study is mainly to describe the performance of primary school teachersin the unit of education technical implementation in Banyumanik, Semarang. This researchwas conducted in January- August 2017. The sample of this research is 162 primaryschool teachers selected by random sampling technique in order to get the same opportunityas sample. The instruments used in this study were the assessment sheets, the RatingSheet consisted of 64 items of question, and 3 indicators of Primary School TeacherPerformance. The results show that each of Implementation of lesson plans is categorizedvery well (90, 9%), the execution of the learning is 83.4%, assessment of learning is good(82.8%). The Overall performance of primary school teachers is categorized good( 85 , 7 % ). In other words, the primary school teachers of the unit of education technicalimplementation in Banyumanik Semarang can arrange the lesson plans, carry out learningand teaching process and assess the learning process in elementary school.